2013
DOI: 10.1021/cn400093z
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Transport of Superparamagnetic Iron Oxide Nanoparticles through Human Brain Capillary Endothelial Cells

Abstract: ABSTRACT:The blood−brain barrier (BBB) formed by brain capillary endothelial cells (BCECs) constitutes a firm physical, chemical, and immunological barrier, making the brain accessible to only a few percent of potential drugs intended for treatment inside the central nervous system. With the purpose of overcoming the restraints of the BBB by allowing the transport of drugs, siRNA, or DNA into the brain, a novel approach is to use superparamagnetic iron oxide nanoparticles (SPIONs) as drug carriers. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 36 publications
6
66
0
Order By: Relevance
“…Some literature reports reinforce this hypothesis of nanoparticles crossing blood vessel walls. Thomsen et al 31 showed using an in vitro model that SPIOs can pass through blood brain barrier, the most tightly and restrictive vascular barrier in the human body. Also, magnetic nanoparticles were shown to penetrate human umbilical vein endothelial cells in vitro.…”
mentioning
confidence: 99%
“…Some literature reports reinforce this hypothesis of nanoparticles crossing blood vessel walls. Thomsen et al 31 showed using an in vitro model that SPIOs can pass through blood brain barrier, the most tightly and restrictive vascular barrier in the human body. Also, magnetic nanoparticles were shown to penetrate human umbilical vein endothelial cells in vitro.…”
mentioning
confidence: 99%
“…Several publications using in vitro cell culture models of the blood-brain barrier proved that 30%-40% of the applied SPIO can cross this obstacle depending on the magnetic field force or/and surface coating. [46][47][48] In vivo studies using rodents have shown that 17%-30% of injected SPIO overcome the intact bloodbrain barrier. 49,50 In humans, a dose of 0.075 mM iron/kg bodyweight, as demonstrated for VSOP, leads to a plasma concentration (S-U) Integrated PI fluorescence intensities of hippocampal slices with or without microglia depletion before (9 DIV) and after (11 DIV) 3.0 mM VsOP-r1 or VsOP-r2 treatment and glut incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxide nanoparticles below 30 nm in diameter are superparamagnetic and have been extensively explored for various diagnostic and potential therapeutic applications in the CNS. The ability of the USPIOs to cross the human BBB is significantly enhanced in the presence of an external magnetic force [90], and combining an external magnetic force with the disruption of tight junctions using D-mannitol significantly improves the permeability of negatively charged iron oxide nanoparticles through the BBB [91]. In addition, as has been described with other nanoparticles, the binding affinity of SPIOs can be modified by binding different molecules to their structure to produce nanoparticles with increased BBB crossing ability, targeting abilities (ligand-receptor mediated or other biomarkers) and fluorescent properties for optical imaging.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%